(3JaSjQ GdJSJQis - (3CHh eMeO Sgd Hf YHO Gddg GdJSJQj,J (B283 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje CNHQfG GdTjN GdhGYX CHh fUQ CMeO Hf YHO GdLHGQ Hf eMeO abGd Hd gh bQBf eLjO Ci cJGH eMce ai dhM eMahX ShQI aGJMI GdcJGH bGd Sgd eYfi GdMeO GdTcQ ddg s
(3BNQgG (B:s
(3jfJgi HCKfGA JaSjQ ShQI GdUa s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjjf HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B143s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJaSjQ hYdhe GdbQBfs